Etruscan Red-Figured Vase-Painting at Caere - Chiaro, Mario A. del (UC Press voices revived., 2020)
This study derives from a close investigation of a class of Etruscan plates belonging to the Genucillia Group. Soon attracted to these products of no great aesthetic merit were many vases of different shapes and more imposing character, also decorated by Caeretan painters. We can now recognize a fairly important and prolific red-figured fabric produced at Caere, an Etruscan city of major significance whose pottery must be fully considered in any future discussion of Etruscan art and civilization. Many vases previously grouped and treated within the more general framework of Etruscan red-figure are now attributed to Caertan potters an vase painters. This disclosure will provide important data for the better understanding of political, commercial and cultural relations between cities within and beyond Etruria during the whole of the 4th century B.C. This title is part of UC Press's Voices Revived program, which commemorates University of California Press's mission to seek out and cultivate the brightest minds and give them voice, reach, and impact. Drawing on a backlist dating to 1893, Voices Revived makes high-quality, peer-reviewed scholarship accessible once again using print-on-demand technology. This title was originally published in 1974.